Influence of ligand's directional configuration, chrysenes as model compounds, on the binding activity with aryl hydrocarbon receptor - Kim, Taewoo; Zhen, Juyuan; Lee, Junghyun; Bauer, Robert; Lee, Changkeun; Kwon, Bong-Oh; Chae, Keun Hwa; Hong, Seongjin; Giesy, John P.; Chang, Gap Soo; Khim, Jong Seong (Nature Publishing Group, 2020)
Understanding what and how physico-chemical factors of a ligand configure conditions for ligand-receptor binding is a key to accurate assessment of toxic potencies of environmental pollutants. We investigated influences of the dipole-driven orientation and resulting directional configuration of ligands on receptor binding activities. Using physico-chemical properties calculated by ab initio density functional theory, directional reactivity factors (DRF) were devised as main indicators of toxic potencies, linking molecular ligand-receptor binding to in vitro responses. The directional reactive model was applied to predict variation of aryl hydrocarbon receptor-mediated toxic potencies among homologues of chrysene with structural modifications such as the numbers of constituent benzene rings, methylation and hydroxylation. Results of predictive models were consistent with empirical potencies determined by use of the H4IIE-luc transactivation bioassay. The experiment-free approach based on first principles provides an analytical framework for estimating molecular bioactivity in silico and complements conventional empirical approaches to studying molecular initiating events in adverse outcome pathways.